EFFECT OF LEADERSHIP, ORGANIZATIONAL CLIMATE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE (Case Study in the Household Subdivision of the Secretariat of the Directorate General of Defense Forces of the Indonesian Ministry of Defense) - Ciswiatni Ciswiatni; Maya Puspita Dewi (Universitas Muhammadiyah Tapanuli Selatan, 2022)
This study aims to determine and analyze the influence of leadership on employee performance, to determine and analyze the influence of organizational climate on employee performance, to identify and analyze employee work motivation on employee performance, to identify and analyze the influence of leadership, organizational climate, and work motivation simultaneously. on the performance of employees in the Household Subdivision of the Secretariat General of Defense Forces of the Ministry of Defense of the Republic of Indonesia. The research method used is a quantitative method with a descriptive approach. As for the population in this study are all employees in the Household Subdivision, amounting to 43 people. The data needed is primary data for the basis of analysis, while the data collection technique is a questionnaire. The results showed that leadership, organizational climate and work motivation have an effect on employee performance in the Household Subdivision of the Secretariat General of Defense Forces of the Ministry of Defense of the Republic of Indonesia